PENGARUH KUALITAS PRODUK, HARGA DAN WORD OF MOUTH (WOM) TERHADAP KEPUTUSAN PEMBELIAN BAJU SEVENTYFOUR PADA BANDUNG SUPER MODEL MALANG - Prihat Agung; M. Hufron; N. Rahma (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
Abstract This study aims to find out and analyze the influence of product quality, price and WOM both simultaneously and partially on purchasing decisions of Seventyfour Clothing in Bandung Super Model Malang. The population in this study is the number of consumers in May, which is 750 which shows the average number of buyers each month. While the number of samples taken is as many as 88 respondents. The results showed that there were effects of product quality, price and wom partially on the purchasing decisions of Seventyfour Clothing in Bandung Super Model Malang. There is the influence of product quality, price and word of mouth simultaneously on purchasing decisions of Seventyfour Clothing in Bandung Super Model Malang.Keywords: Product Quality, Price, WOM, Purchasing Decision